2017
DOI: 10.21307/ane-2017-066
|View full text |Cite
|
Sign up to set email alerts
|

Axonal outgrowth stimulation after alginate/mesenchymal stem cell therapy in injured rat spinal cord

Abstract: Despite strong efforts in the field, spinal cord trauma still belongs among the untreatable neurological conditions at present.Given the complexity of the nervous system, an effective therapy leading to complete recovery has still not been found. One of the potential tools for supporting tissue regeneration may be found in mesenchymal stem cells, which possess anti-inflammatory and trophic factor-producing properties. In the context of transplantations, application of degradable biomaterials which could form a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…In fact, scaffolds promote MSC adhesion and their survival. The effects of cell-seeded biomaterial scaffolds on improved axonal regrowth or enhanced functional outcomes after SCI than scaffolds alone have been shown in many studies ( Hejcl et al, 2010 ; Kim et al, 2016 ; Blasko et al, 2017 ; Peng et al, 2018 ; Zaviskova et al, 2018 ) and reviewed in Libro et al (2017) and Yousefifard et al (2019) .…”
Section: Biomaterials In Combination With Mscs In Sci Treatmentmentioning
confidence: 99%
“…In fact, scaffolds promote MSC adhesion and their survival. The effects of cell-seeded biomaterial scaffolds on improved axonal regrowth or enhanced functional outcomes after SCI than scaffolds alone have been shown in many studies ( Hejcl et al, 2010 ; Kim et al, 2016 ; Blasko et al, 2017 ; Peng et al, 2018 ; Zaviskova et al, 2018 ) and reviewed in Libro et al (2017) and Yousefifard et al (2019) .…”
Section: Biomaterials In Combination With Mscs In Sci Treatmentmentioning
confidence: 99%
“…From a neurodegenerative perspective, it has become increasingly recognized that neuroinflammation plays a significant pathomechanistic role [51]. [53]. Antagonizing the inductive effect of myelin oligodendrocyte glycoprotein (MOG), MSCs-derived exosomes suppress neuroinflammation and show anti-neuroinflammatory and autoimmune suppressive characteristics after SCI.…”
Section: Secretome Of Mscs and Suppression Of Neuroinflammationmentioning
confidence: 99%
“…Besalti et al demonstrated that an early intravenous administration of allogenic MSCs would up-regulate the expression of GFAP by seven days after injury[121]. MSCs transplantation contributes to the formation of a neuroprotective microenvironment by GFAPexpressing astrocytes for neurogenesis[53]. It has been shown that reactive and hypertrophic astrocytes start expressing COX-2 within the area of ischemia in response to pro-inflammatory stimuli[122].…”
mentioning
confidence: 99%
“…Much larger doses of cell transplantation are needed to treat the restrictions of selective permeability of the endothelium on cell infiltration. To circumvent this limitation, dual therapies including stem cells administered with the biomaterial, astrocyte-derived conditioned medium or drugs that transiently open the BBB have been considered [ 47 ]. Antagonizing the inductive effect of myelinoligodendrocyte glycoprotein (MOG), MSC-derived exosomes suppress neuroinflammation and show anti-neuroinflammatory and autoimmune suppressive characteristics after SCI.…”
Section: Introductionmentioning
confidence: 99%
“…Besalti et al demonstrated that an early intravenous administration of allogenic MSCs would upregulate the expression of GFAP by 7 days after injury [ 115 ]. MSC transplantation contributes to the formation of a neuroprotective microenvironment by GFAP-expressing astrocytes for neurogenesis [ 47 ]. It has been shown that reactive and hypertrophic astrocytes start expressing COX-2 within the area of ischemia in response to pro-inflammatory stimuli [ 116 ].…”
Section: Introductionmentioning
confidence: 99%